Smaller heart rate zones improves the precision of the summated-heart-rate-zones training load model in basketball players - Scanlan, A. T.; Fox, J. L.; Poole, J.; Dalbo, V. J. (Journal of Australian Strength and Conditioning, 2017)
The Summated-Heart-Rate-Zones (SHRZ) model is a popular method to quantify internal training load (TL) in basketball players. However, the primary limitation with the SHRZ model is lack of precision in differentiating internal intensities with the use of relative heart rate (%HRmax) zones spanning 10%HRmax. Therefore, this study examined the influence of using smaller relative heart rate zone ranges (5%HRmax and 2.5%HRmax) on the SHRZ TL compared to the traditional 10% zone range during basketball training.